Circulating Collagen Biomarkers as indicators of Disease Severity in Pulmonary Arterial Hypertension - Safdar, Zeenat (2014)
OBJECTIVE: The goal of this study was to determine if biomarkers of collagen metabolism in pulmonary arterial hypertension (PAH) identify patients with worse disease and higher risk of death. BACKGROUND: The relationship between markers of collagen metabolism, degree of disease, and outcome in PAH is unknown. METHODS: Stable idiopathic, anorexigen-associated and hereditary PAH patients were prospectively enrolled. Collagen biomarkers levels were measured: N-terminal propeptide of type III procollagen (PIIINP), C-terminal telopeptide of collagen type I (CITP), matrix metalloproteinsase 9 (MMP-9) and tissue inhibitor of metalloproteinase 1 (TIMP-1). Patients were divided into mild, moderate, and severe PAH groups. Data was compared between tertiles of each biomarker. Pearson correlation and Spearman rank coefficient analyses were performed. Data on time to death or transplantation was examined by Kaplan-Meier survival curves. RESULTS: Circulating levels of PIIINP, CITP, MMP9 and TIMP1 were higher in the PAH group (N=68) as compared to age- and gender-matched healthy controls (N=37) (p<0.001 for each). PIIINP levels increased with the severity of disease (p=0.004). PIIINP tertile data indicated that with increasing levels, six-minute walk distance (6MWD) and cardiac index (CI) decreased and WHO FC worsened, and resting heart rate increased. A significant correlation existed between PIIINP with worsening WHO FC (r(s)=0.319, p=0.008) and a negative correlation with CI and 6MWD (r=-0.304 and -0.361 respectively; p<0.05). PIIINP tertiles showed a trend towards worse outcome in patients with higher tertile (lung transplant or death) (p=0.07, log rank test). CONCLUSIONS: Markers of collagen metabolism were associated with worse disease in PAH patients.